Preventing Resistance — The Role of Optimized Dosing - Buckley, Rita (MD Conference Express, 2011)
The rapid emergence of antibiotic resistance is a major public health concern [Zhang L et al. Appl Environ Microbiol 2011]. This article discusses five questions of resistant bacteria in the gut: Their possible presence without antibiotic exposure; Whether there is selection of resistant gut bacteria during antimicrobial exposure; Whether there is selection of resistance during systemic treatment for other infections; Whether it is possible to avoid or minimize selection; How optimization of treatment relates to selection of resistance in the gut.